Moving limit cycles model of an economic system - Kryuchkov, Vladimir; Solomonovich, Mark; Anton, Cristina (My University, 2017)
We consider a model explaining the dependence between the productivity of labor (PL) and the fixed capital per worker (FC) in an economic system. The core of the model is a nonlinear oscillator with a limit cycle as an attractor. We run numerical simulations of the dynamics specific to this non-autonomous model to compare with the actual data recorded for the years 1987–2001 for the enterprise Omsk Bacon. Based on the numerical analysis we can conclude that the interior dynamics is not affected by exterior perturbations. The numerical simulations can help the managers of the enterprise to take the right steps to avoid stagnation.
Keywords: dynamical system; limit cycle; complex systems modeling; fiber bundle; numerical scheme